A viable approach to prepare 3C-SiC coatings by thermal MOCVD using commercial grade precursors. Issue 11 (September 2022) - Liu, Housheng; Tariq, Naeem ul Haq; Jing, Weichen; Cui, Xinyu; Tang, Mingqiang; Xiong, Tianying
Abstract: A series of 3 C-SiC coatings were prepared by organometallic chemical vapor deposition (MOCVD) using precursor solution containing a varying proportion of commercial-grade hexamethyldisiloxane (HMDSO) and n-hexane. The phase composition, bonding state, and microstructure of 3 C-SiC coatings were studied in detail by grazing incidence X-ray diffraction (GIXRD), Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), and scanning electron microscopy (SEM). The microstructure and mechanical properties of the optimal 3 C-SiC coating were characterized by scanning transmission electron microscopy (STEM) and nanoindentation, respectively. Our results revealed that the amount of undesired graphite phase can be significantly reduced in the 3 C-SiC coating by introducing hydrogen gas in the reaction chamber alongside increasing the ratio of HMDSO/n-hexane in the precursor mixture. The STEM results revealed that the optimal coating was predominantly composed of nano-crystalline 3 C-SiC grains alongside a small amount of amorphous graphite. The hardness and elastic modulus of the optimal coating were 38.19 GPa and 363.2 GPa, respectively.